Can co-created knowledge mobilisation interventions alter and enhance mindlines to improve childhood eczema care? A UK-based Social Impact Framework evaluation - Fiona Cowdell; Stephanie Lax; Julie Van Onselen; Rose Pendleton (BMJ Open)
Objective To evaluate the impact of using knowledge mobilisation interventions to alter and enhance mindlines and improve childhood eczema care.Design The eczema mindlines study involved three stages: (1) mapping and confirming eczema mindlines, (2) intervention development and delivery and (3) analysis of intervention impact. The focus of this paper is on stage 3. Data analysis was guided by the Social Impact Framework to address the questions: (1) what is the impact of this study on individuals and groups? (2) what changes in behaviour and practice have occurred due to their involvement? (3) what mechanisms have enabled these impacts or changes to occur? and (4) what are the recommendations and questions arising from this research?Settings A deprived inner-city neighbourhood in central England and national/international settings.Participants Patients, practitioners and wider community members exposed to the interventions locally, nationally and internationally.Results Data revealed tangible multi-level, relational and intellectual impacts. Mechanisms supporting impact included: simplicity and consistency of messages adapted to audience, flexibility, opportunism and perseverance, personal interconnectivity and acknowledgement of emotion. Co-created knowledge mobilisation strategies to alter and enhance mindlines mediated through knowledge brokering were effective in producing tangible changes in eczema care practice and self-management and in ‘mainstreaming’ childhood eczema in positive way across communities. These changes cannot be directly attributed to the knowledge mobilisation interventions, however, the evidence points to the significant contribution made.Conclusion Co-created knowledge mobilisation interventions offer a valuable method of altering and enhancing eczema mindlines across lay-practitioner-wider society boundaries. The Social Impact Framework provides comprehensive method of understanding and documenting the complex web of impact occurring as a result of knowledge mobilisation. This approach is transferable to managing other long-term conditions.